Fruit and Vegetable Intake is Inversely Associated with Cancer Risk in Mexican-Americans. (17th November 2019) - Wu, Shenghui; Fisher-Hoch, Susan P.; Reininger, Belinda M.; Lee, Miryoung; McCormick, Joseph B.
Abstract: Objective : There is inconsistent evidence and limited data in the Hispanic population concerning fruit and vegetable intake and cancer risk. This study explored the effect of fruit and vegetable intake on cancer risk in Mexican-Americans. Methods : Participants in this cross-sectional study were drawn from the Cameron County Hispanic Cohort. Consumption of fruits and vegetables were assessed using a validated questionnaire. Cancer was self-reported by the participants based on being told by a health care provider that they had cancer. Results : Among 2, 381 participants with available dietary data, 82 reported a diagnosis of cancer. Participants who met recommendations of five or more servings of fruit and vegetable per day had a significantly 86% lower risk for reported cancer compared with those who did not meet recommendations, after adjusting for other covariates. Every portion increment of total fruit and vegetable intake was significantly associated with the reduced cancer risk by 11% with the adjustment of other covariates. Conclusions : Fruit and vegetable intake was inversely associated with cancer risk in Mexican-Americans. Improving the consumption of fruit and vegetable might be an effective area for further research as part of a strategy for cancer prevention and control among Mexican-Americans independent of other factors.